Common Sense dalam Epistemologi George Edward Moore dan Implikasinya terhadap Perkembangan Ilmu - Abbas Hamami Mintaredja (Jurnal Filsafat "WISDOM", 2004)
The birth of Moore's philosophy has a background in Bradley's Idealism-The philosophy of Bradley is rooted in Hegelianistic philosophy- and in Berkeley's immaterialism. Moore tried to revive English Realism tradition. Long before Bradley thoughts. The matterials of this research are all drawn from English philosophy that deals with Common Sense, both influencing and influenced by Moore's philsophy.The objective of this research is describe the function of Common Sense in Moore's philosophy. The aims of this research are (1) to determine the meaning of Common Sense, (2) to determine the realization of epistemology of Common Sense, and (3) to identify the contribution of epistemological Common Sense in the development of philosophy of science. This research uses three methods, (1) Factual-Historical Method, which is used to retrace the stream of development of the meaning of Common Sense in English philosophy. (2) Synthetico-Analitic method, which is used to find out specific meaning of the term Common Sense. (3) Hermeneutics. Which is useng to mediate the messeage drawn from realities (objects).The results of this research are (1) historically, the conception of Common Sense used by many philosophers. Despite differents of terminilogy and meaning according to them. (2) Synthetic-analitically, the meaning of Common Sense depends on the approaches of the respective philosophers. (3) Hermeneurtically, the meaning of Common Sense in Moore philosophy is to be understood as a unifeid ability of sense activities and consciuosness to grasp and understand material objects. Common Sense denotes to human capacity, that is a universal belief that produces certainty of knowledge of material things. Common Sense epistemology is specific ally Moore's epistemology. It is sparates the subjects from the objects distinictively. A subject sees factual objects in direct experiences, so that he gets the sense-data. Tp apprehend sense-data directly involves conscious activity. The result of that activity is the true and necessary knowledge. The contribution of Moore's Common Sense epistemology to the philosophy of science that sense-data of material thing objects are indispensable as a point for developing scientific knowledge. Therefore, Common Sense knowledge is implanted in every stage of scientific thought.